Pengembangan Soft Skill Peserta Didik - Sulaiman Samad; Suardi Suardi (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract: This Community Partnership Program (PKM) partner is SMP Negeri 1 Duampanua, Pinrang Regency. The main problem faced by partners is that developing soft skills in students is not an easy job for teachers to carry out their daily activities. This factual condition, according to the information obtained, is caused by the limited reading material and exercises that can provide inspiration about practices that can develop soft skills of students. In particular, based on the results of interviews with teachers, the specific problems that were the cause of this and were the main priorities of this Community Partnership Program activities, were: (1) the teachers' limited knowledge of various things that can be done to develop soft skills of students; (2) limited skills of teachers in designing / making various soft skill development programs for students; and (3) the low ability of teachers in implementing various programs in developing soft skills of students. The method used is a participatory model training with an icare approach (introduction, connection, application, reflection, and extension). The results achieved are: (1) partners understand various things that can be done to develop soft skills of students; (2) skilled partners designing / making various soft skill development programs for students; (3) partners are able to carry out various programs in developing soft skills of students. Through this result, there are opportunities for students to have the skills needed in the future to knit civilization and work as professionals. In addition, these results also provide great hope for the creation of a conducive teaching and learning process such as being student-centered, taking place collaboratively, and being integrated with real life.